PEMBERDAYAAN MASYARAKAT DESA MELALUI PROGRAM KKN TERINTEGRASI DI DESA MARGALAKSANA - Fadhilah, Astri Maisarah; Fathonie, Moch. Adam Sulthon Noor; Hidayat, Rafi Akbar; Zulfayanti, Syifa Rahma; Mulyadi, Riham Kamus; Helmayanti, Handrini; Putri, Cindy Amelia; Fitriyani, Fitriyani; Dinata, Fadel Ramadhan Iskandar; Putri, Sarah; Sari, Delia Ratna; Febrianti, Salsa; Nurazizah, Siti; Wulandari, Nur Sekar; Natasya, Carolina; Hadi, Muhammad Nadzar; Khairalla, Mahmoud; Alamin, Alan Nurril; Zalukhu, Arifin S.; Gulo, Novita Sari (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Margalaksana Village, located in Cikakak Subdistrict, Sukabumi Regency, West Java, has great potential but faces various development challenges. Like many villages in Indonesia, Margalaksana experiences problems such as a lack of digital promotion to introduce the village's potential, high risk of stunting due to lack of nutritional knowledge, difficulties in marketing local MSME products, disaster mitigation and road safety issues, and the need to improve the quality of education at various levels. Through a participatory approach that directly involves the community, from the observation stage to implementation, targeted solutions can be formulated. This Community Service Program (KKN) aims to increase the village's visibility through digital media, reduce stunting rates through nutrition education and complementary feeding practices, strengthen local MSMEs with branding and marketing strategies, improve disaster mitigation through reforestation programs and the installation of road reflectors, and improve the quality of education through teaching activities in elementary schools and Islamic boarding schools.